Cholinium-based ionic liquids as bioinspired hydrotropes to tackle solubility challenges in drug formulation - Sintra, Tânia E. (2021)
Hydrotropy is a well-established strategy to enhance the aqueous solubility of hydrophobic drugs, facilitating their formulation for oral and dermal delivery. However, most hydrotropes studied so far possess toxicity issues and are inefficient, with large amounts being needed to achieve significant solubility increases. Inspired by recent developments in the understanding of the mechanism of hydrotropy that reveal ionic liquids as powerful hydrotropes, in the present work the use of cholinium vanillate, cholinium gallate, and cholinium salicylate to enhance the aqueous solubility of two model drugs, ibuprofen and naproxen, is investigated. It is shown that cholinium vanillate and cholinium gallate are able to increase the solubility of ibuprofen up to 500-fold, while all three ionic liquids revealed solubility enhancements up to 600-fold in the case of naproxen. Remarkably, cholinium salicylate increases the solubility of ibuprofen up to 6000-fold. The results obtained reveal the exceptional hydrotropic ability of cholinium-based ionic liquids to increase the solubility of hydrophobic drugs, even at diluted concentrations (below 1 mol·kg-1), when compared with conventional hydrotropes. These results are especially relevant in the field of drug formulation due to the bio-based nature of these ionic liquids and their low toxicity profiles. Finally, the solubility mechanism in these novel hydrotropes is shown to depend on synergism between both amphiphilic ions.